The Dynamics of the Islamic Education System in Shaping Character - Hosaini, Hosaini; Fitri, Agus Zaenul; Kojin, Kojin; Alehirish, Mustafa Hamed Mohamed (EDUKASIA, 2024)
This research was written to describe the dynamics of the Islamic education system in shaping national character and its philosophical values in realizing harmony among religious communities. The type of research used is qualitative descriptive research employing Systematic Library Review (SLR) literature sources from several journals, books, and proceedings related to the topic of discussion. The stages of literature mapping gone through in this research were identification, screening, feasibility, and inclusion. Meanwhile, the references used in this research were limited only to reputable international journals. Based on the results of data analysis, it was uncovered that character education is a basic principle that every individual must possess because the character is the main determinant of the good and bad of a person's attitudes, behaviors, and speech. The findings that can be contributed to this research are strengthening character as a projection for the 21st century to become one of the pillars of changing times, which is the main representation of educational success, including moral character and performance character. Moral character is related to faith, honesty, piety, humility and compassion. In addition, the performance characters are hardworking, tenacious, tough, not giving up easily, thorough, and have high loyalty. In the national context, character education is crucial, as the nation's generation is directed to have personality values, which include national values, religious values, integrity values, independence values, and mutual cooperation values.